Picomolar-sensitive β-amyloid fibril fluorophores by tailoring the hydrophobicity of biannulated π-elongated dioxaborine-dyes - An, Jusung; Verwilst, Peter; Hira Aziz; Shin, Jinwoo; Lim, Sung su; Kim, Ilwha; Kim, Yun Kyung; Kim, Jong Seung (Elsevier, 2022)
The pathological origin of Alzheimer's disease (AD) is still shrouded in mystery, despite intensive worldwide research efforts. The selective visualization of β-amyloid (Aβ), the most abundant proteinaceous deposit in AD, is pivotal to reveal AD pathology. To date, several small-molecule fluorophores for Aβ species have been developed, with increasing binding affinities. In the current work, two organic small-molecule dioxaborine-derived fluorophores were rationally designed through tailoring the hydrophobicity with the aim to enhance the binding affinity for Aβ1-42 fibrils —while concurrently preventing poor aqueous solubility—via biannulate donor motifs in D-π-A dyes. An unprecedented sub-nanomolar affinity was found (Kd = 0.62 ± 0.33 nM) and applied to super-sensitive and red-emissive fluorescent staining of amyloid plaques in cortical brain tissue ex vivo. These fluorophores expand the dioxaborine-curcumin-based family of Aβ-sensitive fluorophores with a promising new imaging agent.